Perbandingan Reformasi Birokrasi Pelayanan Pajak Di Indonesia Dan Malaysia Studi Kasus : Prosedur Dalam Pembayarah Pajak - Saputra, M. Aditya Darma; Dompak, Timbul (Prosiding, 2024)
This study compares the tax administration bureaucracy reform between Indonesia and Malaysia, focusing on tax payment procedures. Through comparative analysis, this research evaluates the measures taken by both countries to improve their tax administration systems. Indonesia and Malaysia have implemented various initiatives, including the use of information technology, enhanced transparency, and a focus on tax education to enhance efficiency and taxpayer compliance. Although both countries have differences in political and cultural contexts, they share similarities in efforts to reform tax bureaucracy. This research utilizes qualitative research with a literature review. The findings of this study provide valuable insights for stakeholders in the tax and public administration fields to understand the latest developments and challenges in efforts to improve tax services